Effects of Tree Leaf Litter and Shading on Growth and Yield of Paddy Rice in Northeast Thailand - Patma Vityakon; Sunee Sae-Lee; Surasak Seripong (Agriculture and Natural Resources, 1993)
Earlier results have shown that a tree standing on rice paddy bund enhance soil fertility close to tree base as a result of leaf litter produced, but the higher soil fertility did not translate into higher rice yield relative to the rice grown away from the tree. Shading was deduced to be the cause of low rice yield. The objectives of this study were to determine the effects of quantities of leaf litter and levels of shading on rice growth and yield. A field experiment was conducted with 3 levels of shading, (0-no shading, 20% shading and 50% shading), and 4 levels of leaf litter from Dipterocarpus obtusifolius (i.e. 0, 3.75, 7.50, and 11.25 tons ha-1). The experiment was arranged in split plot design with shading as the main plot and litter quantity as the subplots. There were 4 replications. Each experimental unit was 2x2 m2 of bunded plot. RD-6 rice was grown. Shading resulted in decreased rice yield due to the decrease in various yield components and the increase in unfilled grains. However, plant height was increased under shade. Leaf litter brougth about higher rice yield than that without leaf litter. However, the yield increases due to leaf litter were only significant under reduced light condition. It was suggested that trees to be planted on paddy bund should be selected with their canopy characteristics in mind, as shading was proved to be an important factor negatively affecting rice yield.